The impact of privatisation on firm efficiency, labor market and budget of government: case of Eritrea - Debessay, Robel Netsereab (University of the Western Cape, 2013)
Magister Commercii - MCom === Privatization has become a central feature of the economic policies of nations in the developed and developing world. Eritrea has also embarked on a privatisation program for the state-owned enterprises. It privatised 39 manufacturing enterprises from 1997-2001 in the hope that the enterprises might be restructured into more efficient, profitable, competent and value creating private enterprises. This thesis assessed the impact of privatisation on the operating efficiency, profitability, employment, wages and tax payment of the Eritrean newly privatised manufacturing enterprises. === South Africa